2021
DOI: 10.3389/fnbeh.2021.601275
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Amygdala in Impairments of Affective Behaviors Following Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (TBI) results in chronic affective disorders such as depression, anxiety, and fear that persist up to years following injury and significantly impair the quality of life for patients. Although a great deal of research has contributed to defining symptoms of mild TBI, there are no adequate drug therapies for brain-injured individuals. Preclinical studies have modeled these deficits in affective behaviors post-injury to understand the underlying mechanisms with a view to developing ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 143 publications
(248 reference statements)
2
8
0
Order By: Relevance
“…Results showed an association between increased amygdala thickness and psychological distress symptoms post TBI. This confirms previous findings that link amygdala increased connectivity and activation to impairment in memory, attention and learning on a cognitive level, as well as to depression, anxiety and fear-related behaviors on the emotional domain [60].…”
Section: Somatizationsupporting
confidence: 92%
“…Results showed an association between increased amygdala thickness and psychological distress symptoms post TBI. This confirms previous findings that link amygdala increased connectivity and activation to impairment in memory, attention and learning on a cognitive level, as well as to depression, anxiety and fear-related behaviors on the emotional domain [60].…”
Section: Somatizationsupporting
confidence: 92%
“…The authors reported that only about 13% of the injured animals were found to be "vulnerable, " showing increased exploration of anxiogenic regions during testing compared to baseline behavior and to sham-treated animals (Popovitz et al, 2021). The behavior of the vulnerable mice had neurobiological correlates in the medial prefrontal cortex, basolateral amygdala, and ventral hippocampus; all areas that are associated with stress and anxiety (Almeida-Suhett et al, 2014;Bryant and Barker, 2020;Kenwood et al, 2021;Liu et al, 2021;McCorkle et al, 2021;Pentkowski et al, 2021). Statz et al employed a different "affective profiling" technique to identify "affected" and "unaffected" rats 3 weeks or 6 months following exposure to repeated blast overpressure (Statz et al, 2019).…”
Section: Use Of Multiple Tests and Alternative Data Analysis Methodsmentioning
confidence: 99%
“…Finally, we quantified memory traces in two subregions of the AMG, the BA and CeA, as these are the two primary subregions of the AMG that are essential for expression of fear ( Figures 3A-C ) [31-32]. In the BA, there were no significant differences in the number of EYFP + ( Figure 3D ) or c-fos + ( Figure 3E ) cells between the groups.…”
Section: Resultsmentioning
confidence: 99%